2022
DOI: 10.1051/0004-6361/202142507
|View full text |Cite
|
Sign up to set email alerts
|

The gravitational field of X-COP galaxy clusters

Abstract: The mass profiles of massive dark matter halos are highly sensitive to the nature of dark matter and potential modifications of the theory of gravity on large scales. The Λ cold dark matter (CDM) paradigm makes strong predictions on the shape of dark matter halos and on the dependence of the shape parameters on halo mass, such that any deviation from the predicted universal shape would have important implications for the fundamental properties of dark matter. Here we use a set of 12 galaxy clusters with availa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 143 publications
4
21
0
Order By: Relevance
“…Not only is the normalization of acceleration higher than what is found for galaxies (e.g., Tian et al 2020), but also the overall shape of the observed cluster RAR clearly deviates from the model in Eq. 4, implying a completely different RAR between clusters and galaxies (e.g., Eckert et al 2022;Tam et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only is the normalization of acceleration higher than what is found for galaxies (e.g., Tian et al 2020), but also the overall shape of the observed cluster RAR clearly deviates from the model in Eq. 4, implying a completely different RAR between clusters and galaxies (e.g., Eckert et al 2022;Tam et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We thus ignore the core with a size of 200 kpc in the following discussion. Beyond the core, the contribution of stellar mass in the total mass budget is roughly a constant at ∼ 2% up to 2.5 Mpc (see, e.g., Andreon 2015;Eckert et al 2022). Therefore, we approximate the stellar mass profile M * (r) as 0.02 × M tot (r), adding on a systematic uncertainty of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…6, we have validated the i(cm)z model as a reliable indicator of the level of hydrostatic bias present in the total mass reconstruction. By applying the technique to the X-COP objects, a sample that offers high-quality data from which a detailed analysis of their hydrostatic mass profile has been produced (Ettori et al 2019;Eckert et al 2022), we assessed a level of hydrostatic bias quite in agreement with the current available constraints based on completely different assumptions (e.g., an universal gas mass fraction of reference; see Eckert et al 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…The crosses show the predicted values from the revised scaling laws (orange, f g ; purple, T sl ; and green, L bol ). We further considered the role of the universal pressure profile, in particular, by estimating a profile through a joint fit of the X-COP nonparametric deprojected points from the recent analysis in Eckert et al (2022) and including the corrections due to the nonthermal pressure to M 500 (and, consequently, to R 500 ) from Fig. 7.…”
Section: Constraints On the Hydrostatic Biasmentioning
confidence: 99%
See 1 more Smart Citation